Dark and singular optical solitons perturbation with fractional temporal evolution. (April 2017) - Younis, Muhammad; ur Rehman, Hamood; Rizvi, Syed Tahir Raza; Mahmood, Syed Amer
Abstract: The article studies the dynamics of dark, singular, combined optical solitons and many other periodic solutions to fractional temporal perturbed nonlinear Schrödinger equation in nonlinear optics. The fractional extended Fan sub-equation method is first time used for any fractional temporal nonlinear Schrödinger equation. The solutions are of qualitatively different nature, depending on the five parameters. The constraint conditions, for the existence of the solitons, are also listed. Moreover a couple of other solutions known as combined soliton and combined periodic solution, fall out as a by product in limiting cases. Highlights: The time fractional nonlinear Schrodinger equation describes the propagation of solitons in optical and quantum physics. The existence of the exact solutions for nonlinear time fractional model is of great importance. A rich class of optical solitons is extracted using a single technique.